2015
DOI: 10.3354/meps11225
|View full text |Cite
|
Sign up to set email alerts
|

Brevetoxin-associated mass mortality event of bottlenose dolphins and manatees along the east coast of Florida, USA

Abstract: A mass mortality of bottlenose dolphins Tursiops truncatus and Florida manatees Trichechus manatus latirostris co-occurred with a severe bloom of the toxic algal species Karenia brevis along the eastern coast of Florida, USA, between October 2007 and January 2008. Brevetoxin (PbTx), a potent neurotoxin produced by this marine alga, was detected in 69 and 92% of the tested carcasses of manatees and dolphins, respectively, at concentrations similar to those reported for earlier mortality events along the west co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…Die-off events caused by toxic algae or pathogens could explain not only the population collapse of Posorja but also in the El Morro and in other bottlenose dolphin communities in the inner estuary which show important decreases in abundance in the last decades (Félix et al, 2017). Harmful algal blooms (HABs) have caused massive mortalities of bottlenose dolphins in Florida (e.g., Flewelling et al, 2005;Fire et al, 2015), as well as outbreaks of morbillivirus around the world (Taubenberger et al, 1996;Van Bressem et al, 2014). Red tides are not rare events in the Gulf of Guayaquil and some of them were confirmed to have been toxic (Borbor-Cordova et al, 2019), so it is not ruled out that a mortality event could have happened at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Die-off events caused by toxic algae or pathogens could explain not only the population collapse of Posorja but also in the El Morro and in other bottlenose dolphin communities in the inner estuary which show important decreases in abundance in the last decades (Félix et al, 2017). Harmful algal blooms (HABs) have caused massive mortalities of bottlenose dolphins in Florida (e.g., Flewelling et al, 2005;Fire et al, 2015), as well as outbreaks of morbillivirus around the world (Taubenberger et al, 1996;Van Bressem et al, 2014). Red tides are not rare events in the Gulf of Guayaquil and some of them were confirmed to have been toxic (Borbor-Cordova et al, 2019), so it is not ruled out that a mortality event could have happened at that time.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, a record number of Florida manatee (Trichechus manatus latirostris) mortalities (n = 830) were reported, with one-third of those (n = 276) attributed to prior exposure to an expansive and prolonged red tide bloom. Historically, the majority of red tide blooms in Florida occurred in the southwest part of the state with Sarasota serving as the epicenter [1,2]. This bloom was centered at the mouth of the Caloosahatchee River in Southwest Florida, just south of this epicenter [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, adult survival rates in large mammals tend to vary little across time (Fowler, ). However, large disturbance events in variable environments can affect life‐history processes (Fire et al, ; Moreno & Møller, ). Recent studies reported little annual variation in survival rates for adult female Weddell seals across years that encompassed diverse environmental conditions, including a major iceberg event that led to a decrease in primary productivity (Arrigo, van Dijken, Ainley, Fahnestock, & Thorsten, ; Chambert, Rotella, & Garrott, ; Rotella, Link, Chambert, Stauffer, & Garrott, ).…”
Section: Introductionmentioning
confidence: 99%